Exploring an Interprofessional Staff-Training Model: Application for Teachers and Therapists Working with Children Diagnosed with Autism (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
Increased prevalence of Autism Spectrum Disorder (ASD) has generated higher special needs enrollment in schools requiring teachers and therapists to acquire, incorporate and implement specialized strategies needed to address unique educational and behavioral challenges facing children diagnosed with ASD. Budget cuts have generated a shortage of qualified professionals with expertise in autism interventions. Currently, staff training is minimal, ineffective or lacking on how to do acquire these skills. More effective staff training may provide an avenue for addressing this shortage. This study investigates the impact that an Interprofessional Staff Training Procedure (STP), consisting of Video Self‐Monitoring (VSM), Performance Feedback (PF) and Reflection (R) with and without Mentoring has on sustained and generalized teacher performance on two Dependent Variables – application of the Learn Unit (LU) and Rate of Effective Instruction (ROI). An exploratory study was conducted with 10 female teachers instructing 3‐5 year old autistic children in two private schools utilizing principles of Applied Behavior Analysis. Teacher performance on LU and ROI was evaluated after: Phase 1 – 2‐hour workshop; Phase 2 – training period using STP with and without Mentoring and Phase 3 – follow‐up period when STP and Mentoring are removed. While the STP appeared to enhance teacher performance and sustainability of procedural integrity, the greatest and most consistent improvement in performance was observed among teachers who received STP plus Mentoring as opposed to STP alone. Findings revealed that adding Mentoring to an existing STP appears to enhance teacher performance and Procedural Integrity with sustainable outcome.